Voltage Flicker Mitigation in Electric Arc Furnace using D-STATCOM - Deepthisree Madathil; Ilango Karuppasamy; Kirthika Devi V S; Manjula G Nair (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
The major power quality issue of voltage flicker has resulted as a serious concern for the customers and heavy power companies. Voltage flicker is an impression of unsteadiness of visual sensation induced by a light source whose luminance fluctuates with time. This phenomenon is experienced when an Electric Arc Furnace (EAF) as load is connected to the power system. Flexible AC transmission devices (FACTS) devices were gradually utilized for voltage flicker reduction. In this paper the FACTS device of Distribution Static Synchronous Compensator (D-STATCOM) is used to serve the purpose of mitigating voltage flickering caused by electric arc furnace load, which is efficiently controlled by Icosɸ control algorithm. The model of electric arc furnace is considered as a current source controlled by a non linear resistance, which had been simulated and performance was analyzed using MATLAB/SIMULINK Software.DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.6242